Reformní snahy jansenismu a jejich vliv na osobnost hraběte Františka Antonína Šporka - Bubík, Tomáš (Univerzita Pardubice, 2002)
The first part of the paper focuses mainly on the philosophical and theological analysis of the thoughts of Cornelius Jansen, the founfer of the Jansenism movement. The analysis does not leave aside also the main Jansenists' argument against the contemporary moral laxism, based on the theological probabilism, supported ba the Jesuits. The paper then discusses the influence of Jansenism, especially in Bohemia, in order to point out how important this influence could have been for the formation of the personality of Earl František Špork.
Keywords: teologie; jansenismus; Špork, František Antonín